2001
DOI: 10.4049/jimmunol.166.7.4302
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Ly49E and CD94/NKG2 on Fetal and Adult NK Cells

Abstract: Murine NK cells express inhibitory receptors belonging to the Ly49 and CD94/NKG2 family. Ly49E and CD94 are the only NK cell receptor transcripts detectable in fetal NK cells. Still unproved is the surface expression of Ly49E on NK cells. Here we generated two novel mAbs, a mAb recognizing Ly49E with cross-reactivity to Ly49C, and a mAb against NKG2A/C/E. Ly49E was immunoprecipitated as a disulfide-linked homodimer with 46-kDa subunits. Removal of N-linked carbohydrates revealed a 31-kDa protein backbone. NKG2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
74
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 59 publications
(78 citation statements)
references
References 69 publications
3
74
1
Order By: Relevance
“…Thus, the available data suggest that the majority of Ly49 receptors expressed in B6 mice are specific for classical MHC-I molecules. No MHC-I ligand has been identified for the activating Ly49H, which binds to the MCMV m157 protein (27,28), and no ligand is known for Ly49E, which is predominantly expressed in fetal NK cells and certain TCR␥␦ T cells (17,29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the available data suggest that the majority of Ly49 receptors expressed in B6 mice are specific for classical MHC-I molecules. No MHC-I ligand has been identified for the activating Ly49H, which binds to the MCMV m157 protein (27,28), and no ligand is known for Ly49E, which is predominantly expressed in fetal NK cells and certain TCR␥␦ T cells (17,29).…”
Section: Discussionmentioning
confidence: 99%
“…Ly49 cDNAs in eukaryotic expression vectors have been described before (15,17). Ly49B, C, G2, I, and Q were either subcloned directly or PCR amplified from plasmid DNA and B6 day 14 fetal liver cDNA, respectively, before cloning into a modified pEF-BOS internal ribosome entry site puro expression vector to introduce a NH 2 -terminal vesicular stomatitis virus (VSV) tag.…”
Section: Constructsmentioning
confidence: 99%
“…4J and data not shown). We determined expression of Ly49C by staining with the anti-Ly49C/ Ly49E 4D12 antibody as adult NK cells only contain approximately 1% Ly49E 1 NK cells [32]. There was no difference in the expression of the inhibitory CD94/NKG2A and activating CD94/ NKG2(C-E) heterodimeric receptors ( Fig.…”
Section: Altered Nk Cell Phenotype In Cd70-tg Micementioning
confidence: 99%
“…Despite the data collected on their function, relatively little is known about how the expression of these genes is regulated. Previous studies have shown that nearly all fetal mouse NK cells express CD94/NKG2 on their surface (18) before there is any detectable expression of the Ly-49 genes, with the exception of Ly-49e (19,20). This high frequency of expression decreases after birth, when Ly-49 expression begins to approach adult levels (21,22), and so it appears that there is a developmental switch between the predominate receptors expressed by mouse NK cells.…”
mentioning
confidence: 96%